The Linguistic Philosophy of Noam Chomsky - Mushtaq, Sabahat (sourcecoder, 2022)
Noam Chomsky, one of the most famous linguists of the twentieth century, based his linguistic works on certain philosophical doctrines. His main contribution to linguistics is transformational Generative Grammar, which is founded on mentalist philosophy. He explains the acquisition of language. He claims that it becomes possible for human child to learn a language for the linguistic faculty with which the child is born, and that the use of language for an adult is mostly a mental exercise. His ideas brought about a revolution in linguistics, dubbed as Chomskyan Revolution.